2014
DOI: 10.1007/s00125-014-3408-4
|View full text |Cite
|
Sign up to set email alerts
|

Middle-aged overweight South Asian men exhibit a different metabolic adaptation to short-term energy restriction compared with Europeans

Abstract: Dutch trial registry ( www.trialregister.nl ), trial number NTR 2473.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…We therefore speculate that alterations in metabolic flexibility and mitochondrial aerobic metabolism (Smith et al, 2018) may be a fruitful area for further study. Consistent with this suggestion, a previous small experimental study reported that overweight South Asian men had impaired metabolic flexibility compared with matched European counterparts (Bakker et al, 2015) and we have previously observed poorer oxidative capacity in skeletal muscle independent of diabetes in South Asians compared with Europeans (Jones et al, 2020).…”
Section: F I G U R Esupporting
confidence: 89%
“…We therefore speculate that alterations in metabolic flexibility and mitochondrial aerobic metabolism (Smith et al, 2018) may be a fruitful area for further study. Consistent with this suggestion, a previous small experimental study reported that overweight South Asian men had impaired metabolic flexibility compared with matched European counterparts (Bakker et al, 2015) and we have previously observed poorer oxidative capacity in skeletal muscle independent of diabetes in South Asians compared with Europeans (Jones et al, 2020).…”
Section: F I G U R Esupporting
confidence: 89%
“…However, paradoxically, despite lower cardiorespiratory fitness and fat oxidation during normoglycemic South Asian men had a lower mitochondrial to nuclear DNA ratio, but 349 similar expression of oxidative, lipid and glucose metabolism genes in skeletal muscle (88).…”
mentioning
confidence: 87%
“…Notably, one of those studies demonstrated greater skeletal muscle mass loss during diet-induced weight loss in European American in comparison to African American women who preserved muscle mass 85 . Another study found different metabolic adaptations for South Asian men compared to European men during energy restriction, i.e., improved glucose disposal rate and decreased shift from glucose to lipid oxidation in South Asians 79 .…”
Section: Studies With Only One Diet Group or Non-rctsmentioning
confidence: 96%
“…Ten studies that accounted for race and/or ethnicity in their analyses either examined the pre-post effects of a dietary intervention such as low-fat, high-fiber, fruits, and vegetables diet 77 , verylow calorie diet 78,79 , high-fat high-calorie diet 80 , or alternate-day fasting 81 ; or were a post-diet analysis of an individualized diet 82 , crossover studies of sodium dietary restriction (one dietary intervention) with sodium or placebo supplementation 83,84 , or studies examining one dietary intervention with different physical activity conditioning 85,86 . Notably, one of those studies demonstrated greater skeletal muscle mass loss during diet-induced weight loss in European American in comparison to African American women who preserved muscle mass 85 .…”
Section: Studies With Only One Diet Group or Non-rctsmentioning
confidence: 99%